Association between the Human Development Index and Millennium Development Goals 6 Indicators in Sub-Saharan Africa from 2000 to 2014: Implications for the New Sustainable Development Goals - MLH Mabaso; TP Zama; L Mlangeni; S Mbiza; ZL Mkhize-Kwitshana (Springer, 2018)
It is important to assess whether regional progress toward achieving the millennium development goals (MDGs) has contributed to human development and whether this has had an effect on the triple burden of disease in the continent. This analysis investigates the association between the human development index (HDI) and co-occurrence of HIV/AIDS, tuberculosis (TB), and malaria as measured by MDG 6 indicators in 35 selected sub-Saharan African countries from 2000 to 2014. The analysis used secondary data from the United Nations Development Programme data repository for HDI and disease data from WHO Global Health observatory data repository. Generalized Linear Regression Models were used to analyze relationships between HDI and MDG 6 indicators. HDI was observed to improve from 2001 to 2014, and this varied across the selected sub-regions. There was a significant positive relationship between HDI and HIV prevalence in East Africa (b = 0.048 [95% CI: 0.040-0.056], p < 0.001) and Southern Africa (b = 0.032 [95% CI: 0.002-0.062], p = 0.034). A significant positive relationship was observed with TB incidence (b = 0.009 [95% CI: 0.003-0.015], p = 0.002) and a significant negative relationship was observed with malaria incidence (b = −0.020 (95% CI: −0.029 to −0.010, p < 0.001) in East Africa. Observed improvements in HDI from the year 2000 to 2014 did not translate into commensurate progress in MDG 6 goals.